High temperature heat and water recovery in steam injected gas turbines using an open absorption heat pump. (25th January 2020) - Vandersickel, A.; Wedel, W.G.; Spliethoff, H.
Highlights: Solution to overcome a STIG's low fuel efficiency and high water usage for high return temperatures. Concept for the open absorption heat pump integration in a steam injected gas turbine developed. Full water recovery and increases in fuel efficiency of more than 20% achievable. Heat recovery at high steam injection rates is limited by availability of desorber heating in the HRSG. Possibility to increase electricity generation through heat recovery. Abstract: The advantages of reinjecting steam from the heat recovery steam generator (HRSG) in the preceding gas turbine are increased power and electrical efficiency at low specific cost and a high operating flexibility. The discharge of the injected steam to the ambient has however two major drawbacks: (1) a relevant water consumption and (2) a large thermal loss related to the latent heat of steam. An open absorption heat pump cycle downstream of the HRSG can solve both problems, as it allows to recover the steam from the flue gas and use its condensation heat at elevated temperature. This paper presents for the first time a concept to efficiently integrate both technologies and assesses the potential and limitations of the absorption system for a steam injected gas turbine. For high network return temperatures (60 °C), the "High Temperature Condensation Boiler Technology" (HT-CBT) performs significantly better than a conventional flue gas condenser over the entire STIG operating range, both with respect to fuel efficiency and water recovery. For steam injection rates up to 1.16 kg/s (60 °C) and 0.96 kg/s (40 °C) fuel efficiency remains constant at ca. 95% resp. 102% and power can hence be increased without the associated energetic penalty. Within this range, full water recovery eliminates the high water usage of the Cheng Cycle, making it a suited technology for flexible cogeneration also in dry areas. For higher steam injection rates, the added benefit of the HT-CBT was found to be restricted by the limited availability of desorber heating from the HRSG, suggesting the integration of external desorber heating. The possibility to increase the power output for a given heat demand, with limited impact on fuel efficiency, increases the economic viability of the technology compared to heating only applications.